Hydrogen evolution reaction in the hBNC/Janus MoSSe heterojunction: First-principles calculations - Tian, Lei; He, Chengyu; Peng, Min; Li, Xianrui (International journal of hydrogen energy, 2024)
Hydrogen production from water splitting is a popular subject at present. Therefore, we design the hBNC/Janus MoSSe heterojunctions for hydrogen evolution of photocatalytic water splitting. This investigation is based on the density functional theory. The results indicate that the band alignments of the hBNC/Janus MoSSe heterojunctions are typical type-II. According to the direction of built-in electric field in the heterojunction, we confirm that the hBNC/Janus MoSSe is the direct Z-scheme heterojunction. In addition, the electron mobility and optical absorption coefficient are improved in the hBNC/Janus MoSSe heterojunctions. The hBNC/SeMoS has higher reduction reaction overpotential (χH2 = 3.34 eV) than it (χH2 = 3.06 eV) in the hBNC/SMoSe, while the oxidation reaction overpotential (χO2 = 0.07 eV) in the hBNC/SMoSe is higher than it (χO2 = -0.06 eV) in hBNC/SeMoS. Furthermore, the change of Gibbs free energy under the external potential which is provided by the photoexcited carriers with the light irradiation confirms that the hydrogen evolution reaction is exothermic and could react spontaneously. This work indicates that the hBNC/Janus MoSSe heterojunctions have the potential in hydrogen production of photocatalytic water splitting. [Display omitted] •This paper confirms that the hBNC/Janus MoSSe is the direct Z-scheme heterojunction.•The electron mobility is enhanced in the hBNC/Janus MoSSe heterojunctions.•The optical absorption coefficient is also improved.•The hBNC/Janus MoSSe can spontaneously complete HER.